The Bombay prince - Massey, Sujata (Massey, Sujata. Mystery of 1920s Bombay., 2021)
"November, 1921. Edward VIII, Prince of Wales and future ruler of India, is arriving in Bombay to begin a four-month tour. The Indian subcontinent is chafing under British rule, and Bombay solicitor Perveen Mistry isn't surprised when local unrest over the royal arrival spirals into riots. But she's horrified by the death of Freny Cuttingmaster, an eighteen-year-old female Parsi student, who falls from a second-floor gallery just as the prince's grand procession is passing by her college. Freny had come for a legal consultation just days before her death, and what she confided makes Perveen suspicious that her death was not an accident. Perveen, who strongly identified with Freny-another young Parsi woman fighting hard against the confines of society's rules and expectations-feels terribly guilty for failing to help her. Perveen steps forward to assist Freny's family in the fraught dealings of the coroner's inquest, and when Freny's death is ruled a murder, Perveen knows she can't rest until she sees justice done. But Bombay is erupting: as armed British secret service march the streets, rioters attack anyone with perceived British connections and desperate shopkeepers destroy their own wares so they will not be targets of racial violence. Can Perveen help a suffering family when her own is in danger?"--